Back to School - Badger, Meredith (Australia Hardie Grant Egmont, 2006)
"Back to school with your favourite friends! Score an A+ when you give your child this collection of back-to-school favourites. Join Barney, Bob the Builder, Fireman Sam, Thomas & Friends, and Pingu as they celebrate the fun of learning, meet new friends, and play hide-and-seek in this School day extravaganza. See how fun and learning go hand in hand in these tales of discovery and adventure!"--Container.
Keywords: Fathers and sons -- Friendship -- Schools